Development of a Virtual Laboratory for Biochemistry Practicum during the Covid- 19 Pandemic - Diah Kartika Sari; Jejem Mujamil Sufiana; M. Hadeli; Elsha Melinda; Yeni Oktaria (Postgraduate, University of Mataram, 2022)
Practical lectures should be held face-to-face. The COVID-19 outbreak that hit Indonesia and the world in general made practicum lectures unable to run as they should. This study aims to develop a Virtual Laboratory in the Practicum course. The purpose of this research is to develop a Virtual Laboratory in Biochemistry Practicum. This research is development research with the ADDIE development model from Dick and Carry, namely a development model consisting of five stages which include analysis, design, development, implementation, and evaluation. The results of laboratory development validation show the Aiken coefficient of 0.87 for material experts and 0.92 for media experts. The results of the implementation show practicality of 94.45%. It can be concluded that the virtual laboratory developed in the Biochemistry practicum is valid and practical